2018
DOI: 10.3897/natureconservation.24.20607
|View full text |Cite
|
Sign up to set email alerts
|

Vector analysis: a tool for preventing the introduction of invasive alien species into protected areas

Abstract: Citation: Brancatelli GIE, Zalba SM (2018) Vector analysis: a tool for preventing the introduction of invasive alien species into protected areas. Nature Conservation 24: 43-63. https://doi. AbstractInvasive alien species are the main agent of biodiversity loss in protected natural areas. Prevention is the most appropriate management tool for addressing this challenge, however, virtually all ongoing management efforts are focused on established populations. Although invasion processes include stochastic compon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 57 publications
1
11
0
2
Order By: Relevance
“…Moreover, diligence in recreating historic hydrology likely contributed to producing conditions most conducive to native vegetation. Reference wetlands were publicly accessible and were potentially more susceptible to invasive species establishment due to propagule dispersal through unintentional human transport (Brancatelli & Zalba, ). The lack of invasive plant species on ACEP wetlands as compared to other available wetland habitat indicates that ACEP wetlands are contributing native wetland ecosystems to the wetland matrix in the state.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, diligence in recreating historic hydrology likely contributed to producing conditions most conducive to native vegetation. Reference wetlands were publicly accessible and were potentially more susceptible to invasive species establishment due to propagule dispersal through unintentional human transport (Brancatelli & Zalba, ). The lack of invasive plant species on ACEP wetlands as compared to other available wetland habitat indicates that ACEP wetlands are contributing native wetland ecosystems to the wetland matrix in the state.…”
Section: Discussionmentioning
confidence: 99%
“…Because of this, ACEP sites had more areas of tree stands within the wetland boundary than the reference sites, which were delineated strictly by wetland types and did not in- Previous studies that evaluated plant communities in agricultural landscapes reported a lack of differences in terms of vegetative cover between wetlands located on agricultural land and those that existed within other landscape matrices (Confer & Niering, 1992;Gleason & Rooney, 2017;Gleason et al, 2011;Laubhan & Gleason, 2008;Tapp & Webb, 2015 recreating historic hydrology likely contributed to producing conditions most conducive to native vegetation. Reference wetlands were publicly accessible and were potentially more susceptible to invasive species establishment due to propagule dispersal through unintentional human transport (Brancatelli & Zalba, 2018). The lack of invasive plant species on ACEP wetlands as compared to other available wetland habitat indicates that ACEP wetlands are contributing native wetland ecosystems to the wetland matrix in the state.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the vectors of the spread of these 14 IAPS and their relative importance can be different. Different IAPS can perhaps have different vectors of spread, and frequently, some IAPS have several vectors of spread [88]. IAPS having several vectors can acquire an extensive area of suitability [89].…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…wetland plants so invasive herbaceous species may not colonize the ACEP sites. Reference wetlands were publically accessible, and were potentially more susceptible to invasive species establishment due to propagule dispersal through unintentional human transport (Brancatelli and Zalba 2018). Another invasive wetland plant, common reed (Phragmites australis), was more likely to be found in areas close to point source pollution (Long et al 2017), which indicates that invasive wetland plants can tolerate less-pristine conditions that may exist on the publically accessible reference wetlands included in this study.…”
Section: Discussionmentioning
confidence: 97%